PROMOSI KONTEN UNTUK PEDAGANG PKH - Jessica Grace; Shavira Nurhaliza; Serefina Sibarani; Muhammad Gandung (Abdi Jurnal Publikasi, 2026)
This community service activity aims to improve the digital marketing capabilities of Program Keluarga Harapan (PKH) traders through content promotion strategies. The main problems faced by PKH traders are limited knowledge and skills in utilizing social media as a marketing tool. The methods used include socialization, digital content creation training, and hands-on assistance using social media platforms such as WhatsApp, Instagram, and Facebook. The results show an increase in participants’ understanding and ability to independently create promotional content. This activity is expected to enhance market reach and economic independence of PKH traders.